Hyperlipidemia and Atherosclerotic Lesion Development in Ldlr-Deficient Mice on a Long-Term High-Fat Diet - Ma, Yanling; Wang, Wenyi; Zhang, Jie; Lu, Youli; Wu, Wenyu; Yan, Hong; Wang, Yiping (PLOS ONE, 2012)
Background Mice deficient in the LDL receptor (Ldlr−/− mice) have been widely used as a model to mimic human atherosclerosis. However, the time-course of atherosclerotic lesion development and distribution of lesions at specific time-points are yet to be established. The current study sought to determine the progression and distribution of lesions in Ldlr−/− mice. Methodology/Principal Findings Ldlr-deficient mice fed regular chow or a high-fat (HF) diet for 0.5 to 12 months were analyzed for atherosclerotic lesions with en face and cross-sectional imaging. Mice displayed significant individual differences in lesion development when fed a chow diet, whereas those on a HF diet developed lesions in a time-dependent and site-selective manner. Specifically, mice subjected to the HF diet showed slight atherosclerotic lesions distributed exclusively in the aortic roots or innominate artery before 3 months. Lesions extended to the thoracic aorta at 6 months and abdominal aorta at 9 months. Cross-sectional analysis revealed the presence of advanced lesions in the aortic sinus after 3 months in the group on the HF diet and in the innominate artery at 6 to 9 months. The HF diet additionally resulted in increased total cholesterol, LDL, glucose, and HBA1c levels, along with the complication of obesity. Conclusions/Significance Ldlr-deficient mice on the HF diet tend to develop site-selective and size-specific atherosclerotic lesions over time. The current study should provide information on diet induction or drug intervention times and facilitate estimation of the appropriate locations of atherosclerotic lesions in Ldlr−/− mice.